The Perceptions of People of Color in Academic Libraries Concerning the Relationship Between Retention and Advancement as Middle Managers. Issue 4 (18th May 2016) - Bugg, Kimberley
ABSTRACT: A diverse workforce is important to librarianship. As a result, the recruitment of librarians of color has remained a priority; additionally, ensuring that those individuals are retained and advancing is of equal importance because it speaks to the profession's ability to maintain a diverse workforce. This article explores the interrelationship between retention and advancement for academic librarians of color working as middle managers. Through the use of narrative inquiry, the author found that several commonalities emerged among participants: the prevalence of internal promotions, lack of interest in senior leadership, and participation in library leadership institutes. The findings indicate that retention and advancement are two separate and distinct issues for librarians of color working as middle managers, with retention less of a concern. The findings also suggest that the relationship between the middle manager and his or her supervisor is critical to interest in advancement.